Fig. 3. Trackway S2 in Sauropodomorph dinosaur trackways from the Fleming Fjord Formation of East Greenland: Evidence for Late Triassic sauropods ... - Lallensack, Jens N.; Klein, Hendrik; Milàn, Jesper; Wings, Oliver; Mateus, Octávio; Clemmensen, Lars B. (Zenodo, 2017)
Fig. 3. Trackway S2 (Eosauropus sp.), which probably represents the same trackmaker species, or even the same individual, as trackway S1; trackmaker is moving towards the southwest. A. Photogrammetric orthophoto. B. Depth-color image. C. Interpretative drawing. Abbreviations: LM, left manus; LP, left pes; RM, right manus; RP, right pes. ... : Published as part of Lallensack, Jens N., Klein, Hendrik, Milàn, Jesper, Wings, Oliver, Mateus, Octávio & Clemmensen, Lars B., 2017, Sauropodomorph dinosaur trackways from the Fleming Fjord Formation of East Greenland: Evidence for Late Triassic sauropods, pp. 833-843 in Acta Palaeontologica Polonica 62 (4) on page 837, DOI: 10.4202/app.00374.2017, http://zenodo.org/record/13263609 ...